From Going out Half-Done to Fully Protected: Intrinsic and External Motivators in HPV Vaccine Decision-Making Across Cultures - Alina Cernasev; Karissa Cliff; Hayleigh Hallam; Emily Nagel; Alex Johnson; Tracy M. Hagemann (Women)
Background: The introduction of the human papilloma virus (HPV) vaccine has allowed for incredible strides in the reduction in HPV-related cancers. Despite widespread availability and a recent age group expansion for the vaccine, uptake remains low. Particularly, concerning disparities exist in the state of Tennessee and among minority women. This study aimed to identify key influences of decision-making to receive the HPV vaccine in minority women living in Tennessee. Methods: This study used a prospective, observational, qualitative methods approach. Minority women residing in Tennessee were recruited through flyers posted in various community-based locations around the state. Narrative interviews of participants were conducted until thematic saturation was achieved. Interviewing occurred telephonically, with questions focused on participant perceptions of HPV and its vaccine. Verbatim transcripts were created via external software, and then inductively coded by three researchers. These codes were grouped into categories based on similarities, which facilitated the emergence of themes. Results: A total of 21 participants were interviewed between July and October 2024. Thematic analysis revealed two themes: (1) Awareness of HPV: Determining if the Vaccine is Right for Me; and (2) Intrinsic Motivators for HPV Vaccine adoption: “Like going to the salon and getting your hair half-done”. While some participants had an accurate understanding of HPV, its health consequences, and had received the vaccine, most were unvaccinated and had little understanding of the benefits of this preventative method. Those who received the HPV vaccination were influenced by proactive healthcare workers who provided in-depth education about its benefits. Those who did not elect to receive the vaccine described how its lack of mandate and seldom informational opportunities impacted their decision. Conclusions: Overall, minority women in Tennessee could benefit from improved access to information regarding HPV and its vaccine, as well as direct provider influence and counseling on receiving the vaccine to avoid detrimental health consequences.